“Drive Your Career”: Strategi Meningkatkan Adaptabilitas Karier Melalui Pelatihan Karier - Doddy Hendro Wibowo; Emmanuel Satyo Yuwono (Psympathic : Jurnal Ilmiah Psikologi, 2021)
Career problems experienced by students may indicate that they do not understand their potential, lack of career information, choose wrong majors, doubt about career choices, and do not have a career yet. The purpose of this study is to determine whether the "Drive Your Career" training method can improve students' career adaptability. The training module was developed by researchers and used an experimental research design "one group pretest posttest design". The sampling method used purposive sampling technique involving 46 students of class IX Junior High School (SMP). Career adaptability was measured using the Career Adaptability Scale. The results show that there is an effect of using the "Drive Your Career" training method to improve career adaptability.